Analysis of damage-plasticity model of concrete under uniaxial compression loading - Rafiqul Islam, Mohammad; Ali, Abbas; Jahir Bin Alam, Md.; Ahmad, Tanvir; Sakib, Salman (International Journal of Engineering and Technology, 2021)
Concrete is a quasi-brittle material and shows different behavior in compression and tension. It shows elastic behavior at initial stage and damage-plasticity behavior beyond elastic limit. Therefore, development of material behavior model of concrete is a complex phenomenon. In this study, concrete damage plasticity theory has been described under experiment on concrete cylinder considering uni-axial compression loading and interpreted with analytical data calculated using CEB-FIP model code equation. The code has divided the stress-strain curve for concrete compression into three sections according to concreteâ€™s elastic and non-elastic behaviors. Those three sections have been considered to calculate analytical data. In experiment, concrete behavior has been observed in two phases. The damage value for different stresses at the various points on the stress strain curve has been calculated. According to analytical data, the concrete shows elastic behavior up to 8.3MPa stress point and no damage occur in the concrete within the limit. However, in experimental data, concrete shows elastic behavior up to only 2.28MPa and damage occurred beyond the stress. Finally, the percentage of damage of concrete due to compression obtained from analysis and experiment has been assessed and compared. Above 32 percent of concrete damage is found for 22.5 MPa in both cases.Â Â